2019
DOI: 10.1016/j.chempr.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Neutral ortho Functionalization of Aryl Boroxines via Palladium/Norbornene Cooperative Catalysis

Abstract: A redox-neutral ortho functionalization of aryl boroxines via palladium/ norbornene cooperative catalysis is developed. The ortho amination and acylation are achieved with carboxylic acid anhydrides and O-benzoyl hydroxylamines as an electrophile, respectively, whereas protonation occurs at the ipso position. This transformation avoids using either extra oxidants and reductants or stoichiometric bases and acids. In addition, orthogonal chemoselectivity between aryl iodide and boroxine moieties is demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…These experimental results indicated that both the protons from the ortho -C–H of pinacol arylborate and the adventitious water in the reaction system are the sources for the Catellani termination step, but not the solvent DMSO. The reduction of the deuterium incorporation ratio in eqn (C) and (D) was probably due to the facile H–D exchange with water in the reaction system 8. Thus, these results support the redox-neutral ipso -protonation mechanism proposed in Scheme 1C.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…These experimental results indicated that both the protons from the ortho -C–H of pinacol arylborate and the adventitious water in the reaction system are the sources for the Catellani termination step, but not the solvent DMSO. The reduction of the deuterium incorporation ratio in eqn (C) and (D) was probably due to the facile H–D exchange with water in the reaction system 8. Thus, these results support the redox-neutral ipso -protonation mechanism proposed in Scheme 1C.…”
supporting
confidence: 78%
“…Additionally, allowing us to perform the reaction in air is very attractive from both the practical and economic perspective. Moreover, this process does not require any phosphine or arsine ligand7b,c which is pivotal for previous palladium-catalyzed aminations 35,7a,8. Overall, these practical features make this reaction amenable for industry.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Based on the previous reports on Pd/NBE-catalyzed aryl halide-involved three-component Catellani reaction [50][51][52][53][54][55][56] and our experience on catalytic asymmetric construction of atropisomeric biaryls, 59 reaction mechanism and atroposelectivity of the reported Pd-catalyzed Catellani reaction. As shown in Figure 2, the reaction starts from a solvent coordinated Pd species CP1, which can react with iodonaphthalene reactant 1a through an oxidative addition process via transition-state TS1 with an activation free energy of 8.6 kcal/mol.…”
Section: IV V Ar a A A A A A A A A A A A A A A Amentioning
confidence: 99%
“…In Gu et al's elegant work, 49 the chirality installation took place in the last cross-coupling step involving an achiral palladium (Pd) species. Motivated by the recent progress in Pd/norbornene (NBE) cooperative catalysis in which the functionalization of both ortho-and ipso-carbons of the starting arylhalides could be readily achieved, [50][51][52][53][54][55][56] especially the recent Pd/chiral NBE catalysis which has been successfully employed in asymmetric synthesis, 50,51 we envisioned a strategy for the establishment of optically active atropisomeric biaryl monophosphine oxides using a Pd/chiral NBE catalytic system from aryl iodide and a phosphine oxide-containing aryl bromide via the axially chiral Pd(II) intermediate in Figure 1c. Further trapping by the terminating nucleophile will render a modular platform for the divergent synthesis of enantioenriched biaryl atropisomers (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%